Do Tengmalm’s Owls alter parental feeding effort under varying conditions of main prey availability? - Zárybnická, Markéta; Sedláček, Ondřej; Korpimäki, Erkki (Journal of ornithology, 2009)
We studied the diet composition and behavioural responses to variable food conditions in Tengmalm’s Owls ( Aegolius funereus ). The abundance of main prey (voles and mice) of owls was higher in the Ore Mountains, Czech Republic, than in the Kauhava region, Finland. We monitored nests continuously by a camera system to estimate the feeding frequency and to identify prey items provided to nestlings. We recorded 990 prey deliveries at six nests in the Ore Mountains and 1,679 prey deliveries at nine nests in the Kauhava region. Mice ( Apodemus ) and voles ( Microtus and Clethrionomys ) were the main foods of owls in the Ore Mountains, whereas voles ( Clethrionomys and Microtus ) and shrews ( Sorex ) were the main foods in the Kauhava region. In consequence, on average smaller prey items were brought to nestlings at the Finnish site. However, both absolute and relative (per one nestling) feeding frequency was higher in the Kauhava region, and the biomass available to individual nestlings did not differ between the two areas. Moreover, the Finnish and Czech pairs produced about the same number of fledglings. Our results suggest that male owls are able to maintain the amount of food required for chicks by switching to alternative prey, and to increase their prey delivery rates under conditions of reduced abundance of main food.